The rediscovery of the role of the laity in the mission of the church – with reference to the Baptist Union of southern Africa (BUSA) - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.